Efficient and long-lived quantum memory with cold atoms inside a ring cavity - Bao, Xiao-Hui; Reingruber, Andreas; Dietrich, Peter; Dück, Alexander; Straßel, Thorsten; Pan, Jian-Wei (Nature physics, 2012)
Quantum memories are regarded as one of the fundamental building blocks of linear-optical quantum computation1 and long-distance quantum communication2. A long-standing goal to realize scalable quantum information processing is to build a long-lived and efficient quantum memory. There have been significant efforts distributed towards this goal. However, either efficient but short-lived3,4 or long-lived but inefficient quantum memories5,6,7 have been demonstrated so far. Here we report a high-performance quantum memory in which long lifetime and high retrieval efficiency meet for the first time. By placing a ring cavity around an atomic ensemble, employing a pair of clock states, creating a long-wavelength spin wave and arranging the set-up in the gravitational direction, we realize a quantum memory with an intrinsic spin wave to photon conversion efficiency of 73(2)% together with a storage lifetime of 3.2(1) ms. This realization provides an essential tool towards scalable linear-optical quantum information processing.
Gesehen am 28.09.2018